1989
DOI: 10.3758/bf03202638
|View full text |Cite
|
Sign up to set email alerts
|

Categorization versus distance: Hemispheric differences for processing spatial information

Abstract: It has been hypothesized that the brain computes two different kinds of spatial-relation representations: one used to assign a spatial relation to a category and the other used to specify metric distance with precision, The present visual half-field experiment offers support for this distinction by showing that the left and right cerebral hemispheres make more effective use of the categorization and metric distance representations, respectively. Furthermore, the inclusion of a bilateral stimulus presentation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
147
7
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(174 citation statements)
references
References 19 publications
(40 reference statements)
17
147
7
2
Order By: Relevance
“…In a previous study , we demonstrated baboon's ability to evaluate the distance between line-dot stimuli of the Hellige and Michimata's type (Hellige and Michimata, 1989). The aim of the present research was to extend our finding, by controlling if baboons can categorize line -dot stimuli on an 'above/below' basis.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…In a previous study , we demonstrated baboon's ability to evaluate the distance between line-dot stimuli of the Hellige and Michimata's type (Hellige and Michimata, 1989). The aim of the present research was to extend our finding, by controlling if baboons can categorize line -dot stimuli on an 'above/below' basis.…”
Section: Introductionmentioning
confidence: 52%
“…Although the positive results on pigeons (Kirkpatrick-Steger and Wasserman, 1996) and chimpanzees (Hopkins and Morris, 1989) suggest the use of abstract spatial concepts, these results must be considered with caution, as the authors did not check if the animals could transfer their abilities to either novel stimuli or show them in novel experimental contexts. Hellige and Michimata (1989) and Kosslyn et al (1989) examined performance of human participants when evaluating distances and topological relations. Using stimuli made of a line and a dot, these studies suggested that two types of spatial representations are used in humans.…”
Section: Introductionmentioning
confidence: 99%
“…absolute distance) (e.g. [29,35,36]). One crucial difference between these types of spatial relations is that the former is reference frame dependent (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…above/below) or metric (distance) terms (e.g. [1,29,36,40,60]), with left hemisphere processing more categorical and right hemisphere processing more metric in nature. Finally, the hemispheres also seem to differ in the extent to which they direct attention to global (whole object) or local (object part/feature) aspects of visual stimuli (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A hemispheric specialization for different types of visual attributes has been proposed by Kossslyn et al (1989), Hellige & Michimata (1989) and Rybash & Hoyer (1992) (see Jager & Postma, 2003, for a review). Accordingly, the right hemisphere possesses greater competence for the evaluation of metric coordinate representations, whereas the left hemisphere shows an advantage for the processing of categorical spatial relations.…”
Section: Discussionmentioning
confidence: 99%